2019
DOI: 10.1097/brs.0000000000002858
|View full text |Cite
|
Sign up to set email alerts
|

The Rates of LSS Surgery in Norwegian Public Hospitals

Abstract: Study DesignRetrospective administrative database study ObjectiveTo assess temporal and regional trends, and length of hospital stay, in lumbar spinal stenosis (LSS) surgery in Norwegian public hospitals from 1999 to 2013. Summary of Background DataStudies from several countries have reported increasing rates of LSS surgery over the last decades. No such data have been presented from Norway. MethodsA database consisting of discharges from all Norwegian public hospitals was established.Inclusion criteria were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In line with Davis, our results demonstrate that more men than women received lumbar spine surgery. Several studies on the rates of different types of spinal surgery, such as disc herniation and spinal fusion surgery, have been published 2–11 22. In general, the findings in the present paper are in accordance with the other studies from Scandinavian countries3 5 and Germany,6 which show increased rates for lumbar disc herniation and spinal stenosis surgery.…”
Section: Discussionsupporting
confidence: 91%
“…In line with Davis, our results demonstrate that more men than women received lumbar spine surgery. Several studies on the rates of different types of spinal surgery, such as disc herniation and spinal fusion surgery, have been published 2–11 22. In general, the findings in the present paper are in accordance with the other studies from Scandinavian countries3 5 and Germany,6 which show increased rates for lumbar disc herniation and spinal stenosis surgery.…”
Section: Discussionsupporting
confidence: 91%
“…The 144% increase in decompression surgery rates in Denmark (5.7% yearly) is lower than in a comparable study from Norway showing a 238% increase in decompression surgery from 1999 to 2013 (9.1% yearly) ( 14 ). Compared with the Scandinavian studies, an Australian study ( 15 ) investigating surgery rates for LSS from 2003 to 2013 reported an increase of only 31% (2.7% yearly).…”
Section: Discussionmentioning
confidence: 56%
“…Compared with the Scandinavian studies, an Australian study ( 15 ) investigating surgery rates for LSS from 2003 to 2013 reported an increase of only 31% (2.7% yearly). At the end of the data collection period (2013), the Norwegian study ( 14 ) reported a decompression surgery rate with or without fusion of 39 per 100,000, and the Australian study ( 15 ) had a surgery rate of 27 per 100,000. The surgery rate for decompression with or without fusion in Denmark in 2013 was 49 per 100,000 and thus comparable to Norway, although about 25% higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 The treatment options range from non-surgical approaches such as analgesics, physiotherapy, and epidural corticosteroid injections to surgical methods. In the last few decades, the number of surgical procedures to treat DLSS has worldwide increased steadily [4][5][6][7] -in particular in patients older than 65 years of age 8 -despite debates on mid-to long-term improvement in pain or disability [9][10][11] and a potential higher economic burden of surgery. 4 Despite of an impressive number of published studies, 9,[11][12][13][14][15][16][17][18][19][20][21][22][23] the best treatment strategy for patients with DLSS is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%